"Human rights, revolution and reform in the muslim world" - "Chase, Anthony Tirado" (New Delhi, 2013)
Chase uses a range of local developments as his point of departure, in the process stressing the importance of focusing on the diverse Muslim world rather than on one of its parts. He carefully supports his assertions with examples from contentious "on the ground" debates. Adopting a comprehensive view of human rights, he offers a fresh take on the debates over democracy, free expression, and social rights in Muslim-majority states, as well as on the role of movements within those states in shaping what constitutes global human rights.
Keywords: Human rights